Sex Differences in Suicides among Children and Youth: The Potential Impact of Help-Seeking Behaviour. (May 2013) - Rhodes, Anne E; Khan, Saba; Boyle, Michael H; Tonmyr, Lil; Wekerle, Christine; Goodman, Deborah; Bethell, Jennifer; Leslie, Bruce; Lu, Hong; Manion, Ian
Objective: To describe sex differences in health service use among children and youth who died by suicide. Method: This is a retrospective study of children and youth (aged 10 to 25 years) living in Ontario who died by suicide between April 1, 2003, and December 31, 2007. Coroner records were individually linked to outpatient physician visit, emergency department (ED) presentation, and inpatient stay administrative health care records for 724 people (192 girls and 532 boys). Only 77 (10.6%) were aged 10 to 15 years. The health services types used, number of contacts made, and the last contact were compared in boys and girls. Results: About 80% of subjects had contact with the health care system in the year before their death, typically to an outpatient physician and (or) the ED. However, not all were seen for mental health reasons. Girls had more outpatient physician and ED contact than boys and closer in time to their death. Further, girls were more likely than boys to have contact in more than one setting. Still, boys and girls did not differ in their use of an outpatient psychiatrist, some ED presentations, and in the nature and number of inpatient stays. Conclusions: While most people were seen by an outpatient physician and (or) in the ED in the year before their death, not all received mental health care. Further research is needed to determine whether boys and girls who died by suicide differ from their peers in their health service use to guide preventive interventions.